PEMANFAATAN TUMBUHAN SEBAGAI ZAT ADITIF MAKANAN OLEH MASYARAKAT DESA RASAU JAYA UMUM KABUPATEN KUBU RAYA KALIMANTAN BARAT - Andriyani, Putri; Masriani, Masriani; Muharini, Rini (Jurnal Pendidikan Matematika dan IPA, 2019)
AbstractThe people in Rasau Jaya Umum village Kubu Raya regency have used plants as ingredient food that has been inherited from generation to generation for daily cooking or to make the typical food. The typical food in Rasau Jaya Umum village like Rengginang, crackers, and salted fish. The purpose of research to collect data of plants used as food additives by people in Rasau Jaya Umum village. The respondents were chosen through snowball sampling technique and then given a series of questions using observation sheet. The head in Rasau Jaya Umum village is chosen as the main respondent then proceeded to the traders and home industry owners who produce the typical food. The results showed that there are 18 species of 15 plant families used as natural additives, namely Liliaceae, Zingiberaceae, Amaranthaceae, Oxalidaceae, Rutaceae, Arecaceae, Poaceae, Gnetaceae, Malvaceae, Cactaceae, Pandanaceae, Piperaceae, Polygonaceae, Anacardiaceae, and Myrtaceae.Keywords: plants, food additives, Rasau Jaya Umum village